AIR TRANSPORT AND PASSENGER RIGHTS PROTECTION DURING AND AFTER THE CORONAVIRUS (COVID-19) PANDEMIC (EU and comparative law issues and challenges series (ECLIC), 2021)
A pandemic caused by the COVID-19 has caused disorders and enormous damage in all modes of transport. Carriers as well as transport users have faced great challenges of maintaining traffic. Measures and requirements imposed on them were often obscure, imprecise, and the journey itself was uncertain. Passengers were in fear of whether they would be able to reach their destination, but also whether they will succeed in preserving their health. Carriers, on the other hand, have also sought to adapt and provide passengers with safe transport. Nevertheless, the pandemic caused financial collapse of many carriers, landed the world fleet and closed many airports. Various legal instruments related to the protection of public health are applied in air transport, and they have been adopted within the framework of the World Health Organisation (WHO), the International Civil Aviation Organisation (ICAO) and the European Aviation Safety Agency (EASA), which will be presented in the paper. Various epidemiological measures related to the COVID-19 coronavirus pandemic have been prescribed in air transport, applicable during the journey, which have certain specifics in relation to other modes of transport. The paper will present epidemiological measures as well as the procedure applied when there is a passenger on the flight who shows symptoms of an infectious disease, and new procedures related to transport of goods. It will also address the obligation to complete certain forms and provide various information as well as the obligation to compensate costs for cancelled flights. There is no doubt that the COVID-19 pandemic has a significant economic impact on air transport, and efforts will be made to present measures and provide forecasts for the recovery of air traffic in the period that follows. The paper will also address the question as to whether existing legislation and measures are appropriate, whether relevant international organisations have taken prompt measures to protect and ensure air transport during the pandemic, and whether sufficient measures have been taken to protect the health of passengers on the flight.